Towards a knowledge-based services framework from the value cocreation in public services: the case of the public transport services in the South of Brazil - Bebber, Suélen (My University, 2022)
Recent studies have shown that the efficiency measure of public services organizations is no longer sufficient to satisfy citizens and guarantee the society's welfare and should be achieved from the public value, with a focus on citizens. For this reason, a growing demand to consider the citizens as value co-creators within public services systems has reinforced the importance of developing knowledge that can assist in analyzing and designing such service systems. In a knowledge society, the citizen is an essential actor to help develop knowledge-based solutions to social problems, specifically what concerns public services. Therefore, citizens can contribute by mobilizing their personal knowledge and engage in the co-production of public services as value co-creators of the service ecosystem and, consequently, help improve the public value achieved to all citizenry, resulting in knowledge-based public services. This research approached the service-dominant logic and personal knowledge mobilization theories as a starting point. It aimed to propose a conceptual framework of knowledge-based public services for smart cities from mobilizing citizens' personal knowledge in the value co-creation of public services. The empirical object selected for this study was services managed by the municipal government or municipal public services, more specifically, the collective public transport services of Caxias do Sul. The research method used to meet the objectives adopted a qualitative approach with descriptive and exploratory objectives. The single case study method was chosen, and data collection techniques for data triangulation included semi-structured interviews, secondary data, and direct observation. For the interviews, ten interviewees were selected, including representatives of the municipal management and the public transport service concessionaire, followed by representatives of civil organizations and professionals with experience in this service. The second step of the methodological procedures corresponded to the content analysis of secondary data provided by the Municipal Secretariat of Traffic, Transportation, and Mobility (SMTTM ) from citizens' statements at "Alô Caxias". Finally, the direct observation happened during the Municipal Forum for Popular Evaluation of the Public Transportation System at the Union of Neighborhood Associations of Caxias do Sul headquarters. From the data collection, data analyses were performed using content analysis with the software ATLAS.ti 22 and Excel 2019. Besides answering the objectives proposed in this thesis, a conceptual framework of knowledge-based public services was presented. Theoretically, the study expanded the discussions surrounding the service-dominant logic theory by approaching the concepts of engagement and co-production. It also identified emerging categories that compose the knowledge-based public services framework that aims to support municipal management to engage citizens in planning, design, and delivery of services, as active agents of this process. Of the emerging categories identified, communication and leadership were the most significant, which can give the municipal management directions to raise citizens' awareness of their role in service co-production. [resumo fornecido pelo autor]
Estudos recentes tem mostrado que a medida de eficiência das organizações de serviços públicos já não é suficiente para satisfazer os cidadãos e garantir o bem estar da sociedade e deve ser alcançado a partir do valor público, com foco nos cidadãos. Por esta razão, a crescente necessidade em considerar os cidadãos como cocriadores de valor nos sistemas de serviços públicos reforçou a importância de desenvolver conhecimentos que possam ajudar na análise e concepção desses sistemas de serviços. Em uma sociedade do conhecimento, o cidadão é um ator essencial para ajudar a desenvolver soluções baseadas no conhecimento para os problemas sociais, especificamente no que diz respeito aos serviços públicos. Por conseguinte, os cidadãos podem contribuir com a mobilização do seu conhecimento pessoal e se engajarem na coprodução de serviços públicos, como cocriadores de valor do ecossistema de serviços e, consequentemente, ajudar a melhorar o valor público alcançado para todos os cidadãos, resultando em serviços públicos baseados no conhecimento. Esta pesquisa abordou as teorias da lógica dominante dos serviços e da mobilização do conhecimento pessoal como ponto de partida. Teve o objetivo de propor um modelo conceitual de serviços públicos baseados no conhecimento para as cidades inteligentes, a partir da mobilização do conhecimento pessoal do cidadão na cocriação de valor nos serviços públicos. O objeto empírico selecionado para esse estudo foi serviços geridos pelo governo municipal ou serviços públicos municipais, mais especificamente, o serviço de transportes coletivos de Caxias do Sul. O método de pesquisa utilizado para cumprir com os objetivos adotou uma abordagem qualitativa com objetivos exploratório e descritivo. O estudo de caso único foi escolhido, e as técnicas de coleta de dados para a triangulação de dados incluíram entrevistas semi-estruturadas, dados secundários e observação direta. Para as entrevistas, dez respondentes foram selecionados, incluindo representantes da gestão municipal e da concessionária do serviço de transporte público, seguido de representantes de organizações civis e profissionais com experiência nesse serviço. O segundo passo dos procedimentos metodológicos corresponderam a análise de conteúdo dos dados secundários disponibilizados pela Secretaria Municipal de Trânsito, Transporte e Mobilidade (SMTTM) a partir das declarações dos cidadãos no "Alô Caxias". Por fim, a observação direta ocorreu durante o Fórum Municipal de Avaliação Popular do Sistema de Transporte Público que ocorreu na União de Associações de Bairros de Caxias do Sul. A partir da coleta de dados, a análise de dados foi realizada com a análise de conteúdo utilizando os softwares ATLAS.ti 22 e Excel 2019. Além de responder os objetivos propostos por esta tese, um framework conceitual de serviços públicos baseados em conhecimento foi apresentado. Teoricamente, o estudo expandiu as discuções acerca da teoria da lógica dominante dos serviços abordando os conceitos de engajamento e coprodução. Categorias emergentes que compoem o framework de serviços baseados em conhecimento também foram identificadas que visam dar suporte à gestão municipal para engajar os cidadãos no planejamento, desenho e entrega dos serviços, como agentes ativos nesse processo. Das categorias emergentes identificadas, a comunicação e a liderança foram as mais significativas, dando direcionamentos à gestão municipal para conscientizar os cidadãos do seu papel na coprodução dos serviços. [resumo fornecido pelo autor]
Keywords: Transporte - Rio Grande do Sul; Serviço público; Cidades inteligentes; Administração pública; Transportation - Rio Grande do Sul (Brazil); Civil service; Smart cities; Public administration